O uso de sinônimos na produção de artigos de opinião no 9º ano ensino fundamental - Sousa , Jailton Barbosa de (2020)
The study of the lexicon aimed at teaching synonyms has become a secondary interest in teaching activities, carried out in an irrelevant and insignificant way from the point of view of the sociodiscursive uses of the language. Thus, the concept of its use is still valid through exercises whose objective is to form loose sentences or to substitute words in pairs of sentences, assigning them a certain value of semantic equivalence. In view of these difficulties, it was found relevant to study the synonyms, not as isolated words, but as expressions that is how contiguity relations when applied in a given context. Thus, this research aimed to study the use of synonyms, within a cohesive perspective, in the production of opinion article texts, in a ninth grade class at a municipal school in Brejo da Madre de Deus - PE. For this, this work was based on the conception of Antunes (2016, 2012, 2010, 2009, and 2007), that addresses synonyms within a cohesive perspective, which included the exploration of semantically related words, from a given context. Within the same perspective, there were contributions from Koch and Elias (2014, 2017), Koch (2016), Ilari (2002), among others. In this sense, this work developed an action research of an interventional nature when using a methodology that sought the study of the use of synonyms from reading and text production workshops through a sequence of activities, using the opinion article as a vehicle. In this respect, for the study of synonyms, the intervention process involved stages such as reading, interpretation, planning, writing and rewriting. To develop these workshops, the theoretical contribution of Faraco and Terza (2014), Abaurre (2007), Bortoni-Ricardo (2008), among others, was used as a reference. Thus, this research was of great prominence for students in the ninth year of regular education, as it contributed, through the proposed methodology, so that they could expand their linguistic repertoire, combined with the repertoire they acquired during activities.